Social and cultural perspectives of bel canto tradition among urban Chinese communities in Peninsular Malaysia - Phang, Kong Chien (2016)
The emergence of bel canto singing among Malaysian Chinese which can be traced back in the 1930s has largely remained an unexplored field in modern cultural and literary study. This thesis represents, among others, the earliest musicological effort to look into the bel canto singing tradition appropriated among Malaysian Chinese, inquiring questions of how canto bel started initially, how it is sustained throughout the decades and in what means it has appeared to represent in the cultural facade within the Malaysian Chinese communities.This thesis begins by outlining a chronological development of bel canto tradition which became apparent in 1930s featuring a group of Wuhan musicians and is followed by findings of recent discoveries of bel canto activities accumulating to new comprehension of bel canto singing tradition in nowadays Malaysian Chinese communities. Positioning myself in a role as a researcher-cum-practitioner, I essentially adopted Hall's reception theory in this study decoding cultural meanings from data encoded by the composers, producers/organizers in respective cultural artifacts, socio-cultural events and behaviors. Specifically, I focus on cultural signifiers of which their representation has been embraced and participated within the bel canto singing tradition.Discussion of representative repertory contributed by selected prominent composers and the analysis of musico-poetic elements projected by their musical works are deemed the main cultural contributors in constructing Malaysian Chinese-ness in an overarching bel canto tradition. This thesis further explores several cultural signifiers in the process of constructing Malaysian-Chinese-ness in bel canto tradition theorizing this phenomenon in various musicological/sociological/cultural discourses using Nederveen Pietersen's three-paradigm cultural theory and Bourdieu's concepts of habitus and fields.The Malaysian Chinese bel canto tradition is indeed a unique post-modern cultural singularity of which Malaysian Chinese communities earnestly sustain and uphold. This sustenance of bel canto habitus in Chinese communities are continually enacted through cultural signifiers of musical artifacts, musical venues and musical events of which traditional ideology of Chinese-ness is largely projected and ethnic "otherness" is basically uninvolved. Albeit non-Chinese elements are incorporated in the enactments of bel canto habitus since 2000s, Chinese communities remain the central cohort in the operation projecting an atomistic social situation that faced by the current post-modern condition in Malaysia, of which cultural events are still very much ethnic and community based.